ASIMILASI ISLAM DENGAN BUDAYA LOKAL DI NUSANTARA - Mukhlishin, Ahmad; Jamil, Muhammad; Maba, Aprezo Pardodi (Nurani, 2018)
Islam as a religion that is present in all tribes in the archipelago as a value system that integrates with the local culture, so this is often seen by people outside the tribe with Islam Minangkabau, Javanese Islam, and so on. The accumulation of cultures with various intercourses called multiculturalism. But the great possibility both can play an important role in shaping a new culture, because there is a dialogue between the orders of religious values ​​that become the idealism of a religion with local cultural values. As a system of knowledge, religion is a belief system that is full of moral teachings and guidance of life must be studied, examined and then practiced by man in his life. In this case religion provides clues about the "good and bad that are inappropriate and inappropriate" and the "right and inappropriate". Religious values ​​can form and develop human behavior in their daily lives. It is therefore not difficult to understand that having a common symbol is the most effective way to strengthen unity among religious followers. This is because the meaning of these symbols deviates far from the intellectual definitions so that the symbol's ability to unite is greater, whereas the intellectual definition causes division. Symbols can be shared because they are based on feelings that are not formulated too tightly. That is why Islam has historically come to various parts of the archipelago with a relatively peaceful atmosphere with almost no tension and conflict. Islam can easily be accepted by society as a religion that brings peace, even though at that time people have been religious and have their own belief in animism, dynamism, Hinduism and Buddhism. The spread of Islam causes the emergence of Islamic patterns and variants that have uniqueness and uniqueness. It must be realized that the existence of Islam in Indonesia is never single.